“… and he flew out of the window on a wooden spoon” - Thomson-Wohlgemuth, Gaby (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2007)
AbstractTranslation may be viewed in part as a transfer of cultural elements from one text to another and, under certain circumstances, this may occur between texts written in the same language. This is indeed the situation researchers find when analysing the early East German versions of the Brothers Grimm’s fairy tales and comparing them with their (same language) originals. East Germany was a country with a mission to overcome capitalist thinking and to create a new kind of society. Motivated by this, the establishment permitted only certain kinds of texts to reach their audiences. One of the genres vehemently debated in the early days was fairy tales and particularly so the Grimms’ tales due to their high standing in the Third Reich. This article explores the first ‘translations’ of the Grimms’ fairy tales in East Germany, investigating elements that were regarded as ideologically valuable and hence emphasized in the texts and those that were deemed harmful to a socialist education and hence modified.